Ecocritical Approaches to Italian Culture and Literature : the Denatured Wild. - Ardeni, Viola (Ecocritical theory and practice., 2016)
By recognizing the groundbreaking work of many non-Italian ecocritics, and linking to the homegrown contributions of Serenella Iovino, Marco Armerio, and Giovanna Ricoveri, the authors of Ecocritical Approaches to Italian Culture and Literature: The Denatured Wild, challenge the narrowly defined conventions of Italian Studies and illuminate the complexities of an Italian ecocriticism that reveals a rich environmentally engaged literary and cultural tradition.